DEVELOPING ENGLISH EVALUATION INSTRUMENT ON READING SKILL BASED ON CONTEXTUAL TEACHING LEARNING (CTL) - Fitri Palupi Kusumawati (Intensive Journal, 2018)
Reading in one of essensial ways in developing our knowledge. Reading involves many complex skills that have to come together in order to the reader to be successful. One of them is Contextual Teaching Learning (CTL). Evaluation is the proses of scoring in the education field or concernig that related to education activity. The main objective of the research is to develop English materials for reading skill based on CTL. The design of this research is developmental research. The researcher uses formative research. The researcher uses readability and implementability to know whether the prototype was applicable or not. Expert review give suggestion to improve the material, and the researcher also uses the information from one-to-one to improve the product. It is to get the second prototype. In small group, the researcher got a good response, but there are some revise needed. It is to get the third prototype. And the last is field test, in this step the researcher still needs to revise the prototype. It is to get the final prototype. It is concluded that CTL can be used to develop reading material. In field test, the researcher got a good response from the students. It means that this prototype is successful, and it can be applied in the first semester of Civil Engineering Students at Muhammadiyah University of Metro.